Integrative analysis of 115 transcriptomic studies decodes the molecular landscape of neurodevelopmental disorders - Jarno Koetsier; Lars M. T. Eijssen; Leon J. Schurgers; Leopold M. G. Curfs; Chris P. Reutelingsperger; Nasim Bahram Sangani (Communications Biology)
Abstract Due to the low disease prevalence, transcriptomic studies of neurodevelopmental disorders (NDDs) often face limited statistical power, constraining the depth of insights they can provide. To tackle this limitation, we integrated 151 human RNA sequencing datasets from 115 independent studies, and characterized the common and distinct molecular pathways of NDDs and their neurological phenotypes. In addition to revealing an aberrant expression profile of imprinted genes, our analysis identified transcriptomic changes in inflammatory, translational, mitochondrial, and synaptic processes across the different NDDs. We further highlight disorder-associated alterations, including upregulation of ITGB4 across Rett syndrome datasets. Moreover, gene expression changes in LHX1/5-mediated cerebellar Purkinje cell layer formation were found to be specific to seizure-associated NDDs. We combined the datasets into a publicly accessible NDD transcriptomic atlas: https://SyNUM.shinyapps.io/NDD-transcriptomic-atlas/ . Together, our findings provide fundamental insights into the molecular pathophysiology of NDDs and highlight genes and pathways with aberrant transcriptomic profiles. This knowledge can guide future therapeutic development and precision medicine approaches.